An Assessment of Seasonal Variation of Waste Generation and Management in Cross River State, Nigeria - Ukwayi, Joseph K.; Essoh, Peter A; Inah, Sylvester Abam (Richtmann Publishing, 2012)
The level of waste generation and management in Ugep and Ikom urban are of great concern to many scholars inenvironmental management .This paper attempt to assess the seasonal variation of waste generation and management in thetwo urban centre in Cross River State. One hundred and five copies of questionnaire were randomly distributed in each of urbancentre to the residents in three major streets in the area. Information such as flash points, dump sites, types of waste and thefrequency of waste disposal were captured in the questionnaire. Findings shows that there was no significant different in theseasonal variation of urban waste generation and management in the two areas under investigation which was evidenced in thetested hypothesis with high calculated value greater than the critical value of 1.56 at 0.05 level of significance. The fisher ISDtest was further used to buttress the above assertion and the result indicate that family size influence the amount of wastegeneration in the two areas. However, the sustainability of the environment in these two areas depends on the variousstakeholders in area